EARLY GROWTH AND STAND VOLUME PRODUCTIVITY OF SELECTED CLONES OF Eucalyptus pellita - Teguh Setyaji; Sri Sunarti; Arif Nirsatmanto (Secretariat of Agency for Standardization of Environment and Forestry Instruments, 2016)
Using current technologies, several forest plantation companies in Indonesia are pursuing clonal forestry program with E. pellita to increase plantation productivity using selected clones. This paper evaluates the early growth and stand volume productivity of selected clones of E. pellita as part of a breeding program for pulpwood. Two clonal trials of E. pellita were established in Central Java with two different plot configurations: single tree-plot and multiple tree-plot. Trial evaluation was done at two years age involving tree height, diameter, stem volume and stand volume. Result show that among the clones there were significant differences for all traits assessed. All of the tested clones exceeded the control seedling of F-1 generation by 9-50% for height, 10-36% for diameter and 22-137% for stem volume, respectively. Clonal repeatability ranged from 0.7-0.9, with corresponding individual ramet repeatability ranged from 0.2-0.4. Overall stand volume productivity at given age reached 15 m³/ha.